Highly textured Ti2AlN ceramic prepared via thermal explosion followed by edge-free spark plasma sintering. (15th July 2017) - Liu, Yi; Li, Yingxin; Li, Fan; Cui, Han; Pu, Yongping; Guo, Shouwu; Shi, Zhongqi
Abstract: Highly textured Ti2 AlN ceramic was successfully fabricated by edge-free spark plasma sintering (EFSPS) of Ti2 AlN discs synthesized by thermal explosion (TE). The orientation degree of as-sintered Ti2 AlN ceramic was evaluated by X-ray diffraction and electron backscattered diffraction. It was found that the preferred orientation of Ti2 AlN grains paralleled to the SPS-loading direction was along the c -axis and the Lotgering orientation factor on the textured top surface was as high as f (00 l ) = 0.80. Due to the highly textured microstructure, the obtained Ti2 AlN ceramic showed anisotropic mechanical and physical properties. The results highlight the advantages of EFSPS combined with TE technique. Graphical abstract: